2016
DOI: 10.5713/ajas.15.0673
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Wet Distillers Grains on <i>In vitro</i> Ruminal Fermentation and Its Effects on Performance and Carcass Characteristics of Finishing Hanwoo Steers

Abstract: Two experiments were conducted to determine the nutrient composition, in vitro ruminal ammonia concentrations and pH of wet distillers grains (WDG, produced from tapioca 70% and rice 30%) and to evaluate dietary effects of fermented total mixed ration (TMR) using WDG on the performance, blood metabolites and carcass characteristics of Hanwoo steers from mid fattening to slaughter. In Exp. I, average dry matter (DM), crude protein, ether extract, crude fiber, ash, neutral detergent fiber, acid detergent fiber, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…During this period, energy and nutrient requirements increase with an increase in weight and body fat. However, the high-energy level of feed may decrease ADG because of the decrease in intake [57]. Therefore, this study indicated that the increased energy level does not improve the ADG in the late-fattening period of Hanwoo steers.…”
Section: Discussionmentioning
confidence: 66%
“…During this period, energy and nutrient requirements increase with an increase in weight and body fat. However, the high-energy level of feed may decrease ADG because of the decrease in intake [57]. Therefore, this study indicated that the increased energy level does not improve the ADG in the late-fattening period of Hanwoo steers.…”
Section: Discussionmentioning
confidence: 66%
“…During this period, energy and nutrient requirements increase with an increase in weight and body fat. However, the high-energy level of feed may decrease ADG because of the decrease in intake [47]. Therefore, this study indicated that the increased energy level does not improve the ADG in the late-fattening period of Hanwoo steers.…”
Section: Discussionmentioning
confidence: 66%
“…Lee (2017) reported that there was no difference in the ADG and FCR between the control (TDN 72.21%) and the high energy treatment (TDN 75.96%). In contrast, Ahn et al (2016) reported that the ADG and FCR of the treatments with lower TDN were better than those of the control.…”
Section: Resultsmentioning
confidence: 85%